Haemophagocytic lymphohistiocytosis complicating visceral leishmaniasis in the UK: a case for detailed travel history, a high index of suspicion and timely diagnostics. Issue 7 (10th July 2019) - Johnson, Sarah May; Gilmour, Kimberly; Samarasinghe, Sujith; Bamford, Alasdair
Abstract : A 4-month-old male infant presented acutely unwell with fever. He was initially treated for sepsis but failed to improve with IV broad spectrum antibiotics. Haemophagocytic lymphohistiocytosis (HLH) was diagnosed due to his fever, pancytopenia, splenomegaly, hypertriglyceridaemia, hypofibrinogenaemia and significant hyperferritinaemia. An array of differentials for HLH including both immunological and infectious causes were considered and excluded. He had travelled to Madrid, and hence visceral leishmaniasis (VL) was suspected, but was not confirmed on the initial bone marrow aspirate (BMA) microscopy or culture. He improved with empirical treatment with dexamethasone and liposomal amphotericin B. VL was later confirmed on BMA PCR. He made a good recovery and remained well at 12 month follow-up. Non-endemic countries need rapid and sensitive VL diagnostics. A thorough travel history and high clinical index of suspicion are necessary to avoid the pitfall of treatment with intense immunosuppression recommended in treatment guidelines for HLH.